2004
DOI: 10.1042/cs20030161
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent altitude exposures reduce acute mountain sickness at 4300 m

Abstract: Acute mountain sickness (AMS) commonly occurs at altitudes exceeding 2000-2500 m and usually resolves after acclimatization induced by a few days of chronic residence at the same altitude. Increased ventilation and diuresis may contribute to the reduction in AMS with altitude acclimatization. The aim of the present study was to examine the effects of intermittent altitude exposures (IAE), in combination with rest and exercise training, on the incidence and severity of AMS, resting ventilation and 24-h urine vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 32 publications
6
74
0
Order By: Relevance
“…Studies have reported conflicting results regarding intermittent normobaric or hypobaric hypoxic exposures, with some studies showing benefit [107] and others not demonstrating a clear effect [108,109]. One of the challenges in interpreting these discrepant results is that the hypoxic exposure protocols vary significantly between studies with regard to the magnitude and duration of the hypoxic exposures.…”
Section: Preacclimatisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported conflicting results regarding intermittent normobaric or hypobaric hypoxic exposures, with some studies showing benefit [107] and others not demonstrating a clear effect [108,109]. One of the challenges in interpreting these discrepant results is that the hypoxic exposure protocols vary significantly between studies with regard to the magnitude and duration of the hypoxic exposures.…”
Section: Preacclimatisationmentioning
confidence: 99%
“…While these preacclimatisation strategies may carry benefit and probably pose little risk, implementation may be difficult for many travellers and the optimal approach remains unclear. Infrequent and/or short exposures to hypoxia are unlikely to reduce the incidence of AMS [109,110], while longer and/or more frequent exposures are necessary to reduce the risk of altitude illness [107,111]. Such exposures should be performed as close in time to the planned high-altitude travel as possible.…”
Section: Preacclimatisationmentioning
confidence: 99%
“…In all cases, when significant main effects or interactions were found, Newman-Keuls post hoc test was applied. Recent studies of similar experimental procedures using unacclimatized SL volunteers were consulted to determine appropriate sample sizes for the major hypothesis related to changes in PET CO 2 , AMS symptomatology, and exercise performance (3,12,23). It was assumed that sham treatment would have no effect on PET CO 2 and that the magnitude of changes in PETCO 2 induced by NH treatment would be similar to that induced by HH treatment of a similar cohort of six volunteers (2).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…What has not been established, however, is whether NH exposure is any more effective than no treatment for mitigating undesirable outcomes such as AMS or the initial large impairment in exercise performance during subsequent HH residence (22). The only controlled, experimental studies reporting that AMS, exercise performance, and other physiological outcomes were affected favorably relative to no treatment utilized HH treatment prior to HH residence (2)(3)(4)18) or NH treatment prior to NH residence (17,22). Until two other studies were published recently (5,27), no data existed to determine directly whether NH treatment would be more beneficial than no treatment during subsequent HH residence.…”
mentioning
confidence: 99%
“…They exposed the subjects for consecutive days simulating 6000 m (354 mm Hg) for 5 h and 8000 m (270 mmHg) for next 1 h observed an increase in V I and PaO 2 in hypobaric hypoxia, indicating the initiation of ventilatory acclimatisation. The training in intermittent normobaric hypoxia at sea level and its effect on AMS is very limited 16,17 . Today there is only one study that has reported the use of normobaric hypoxic exposure during sleep at sea level and its effect on AMS during subsequent exposure to hypobaric hypoxia 18 .…”
Section: Introductionmentioning
confidence: 99%